Transitioning to a Platform Business: A Resource-Based View Case Study of a South African Bank - Ramrup, Kashil (University of the Witwatersrand, Johannesburg, 2022)
Traditional incumbent banks have seen upstart digital-only banks and fintech, free of legacy systems, challenging their market share. In an effort to avoid disruption by fintechs, banks are embracing the platform strategy. Developing a platform makes it possible to interact with current communities and benefit from shared network effects that can hasten growth, save costs, and increase brand awareness. This research report investigates the impact on a large incumbent bank's resources transitioning to a platform business. A case study was completed on one of South Africa’s big five banks, focusing on the corporate and investment banking(CIB) division. The division is considered a thought leader around platforms within the bank and is actively engaged in shaping and driving its transitional journey. A qualitative study was conducted through semi-structured interviews with senior management and executive leadership. The study population comprised employees of the CIB division of Bank X, South Africa. The sample was selected based on seniority and exposure to the bank's platform business strategy formulation and implementation. The study found that, despite the bank intentions to pursue the platform strategy, there was an internal misalignment in precisely what it meant at the various levels within the organisation, compounded by the lack of platform and technical skills in multiple areas to support the transition. As CIB is a high-touch banking model, there was little understanding of how the physical network would be impacted or could be leveraged/integrated into the platform model. It also found that transitioning to a platform requires individuals with a platform thinking mindset, the ability to challenge the traditional linear pipeline business model, and an enabled and aligned culture with a new operating model that could blend the physical and digital worlds
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: RBV; Platform business; Banking; Resources; Competitive advantage; Transition; Resource based view; UCTD; SDG-8: Decent work and economic growth